2022
DOI: 10.1080/15476286.2022.2139113
|View full text |Cite
|
Sign up to set email alerts
|

Psychrophilic phage VSW-3 RNA polymerase reduces both terminal and full-length dsRNA byproducts in in vitro transcription

Abstract: RNA research and applications are underpinned by in vitro transcription (IVT), but RNA impurities resulting from the enzymatic reagents severely impede downstream applications. To improve the stability and purity of synthesized RNA, we have characterized a novel single-subunit RNA polymerase (RNAP) encoded by the psychrophilic phage VSW-3 from a plateau lake. The VSW-3 RNAP is capable of carrying out in vitro RNA synthesis at low temperatures (4–25°C). Compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…This chimeric SARS-CoV-2 mini-genome dsRNA was prepared by in vitro transcription (IVT) of the positive-sense and negative-sense strand RNA, following by annealing both strands into dsRNA. To prevent interference from dsRNA by-products generated during in vitro transcription, we utilized VSW-3 RNA polymerase (Xia et al, 2022), which has previously been demonstrated to effectively reduce these by-products. Furthermore, to exclude the effect of potential nuclease contamination, we purified both the wild-type SARS-CoV-2 nsp15 with a 6× His tag at the N-terminus and its active-site mutant, H234A, as a control for the cleavage reaction, by metal affinity chromatography and gel filtration chromatography (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…This chimeric SARS-CoV-2 mini-genome dsRNA was prepared by in vitro transcription (IVT) of the positive-sense and negative-sense strand RNA, following by annealing both strands into dsRNA. To prevent interference from dsRNA by-products generated during in vitro transcription, we utilized VSW-3 RNA polymerase (Xia et al, 2022), which has previously been demonstrated to effectively reduce these by-products. Furthermore, to exclude the effect of potential nuclease contamination, we purified both the wild-type SARS-CoV-2 nsp15 with a 6× His tag at the N-terminus and its active-site mutant, H234A, as a control for the cleavage reaction, by metal affinity chromatography and gel filtration chromatography (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…However, some adverse effects of mRNA vaccines, such as hepatitis [138], allergic reactions caused by polyethylene glycol (PEG) [139], and viral reactivation [140], still require researchers to improve vaccine production technologies or delivery systems continuously. To date, self-amplified and trans-amplified mRNA vaccines, delivery systems targeting specific tissues (such as targeting the lung [141]), core-shell structured lipopolyplex (LPP) [142] delivery systems, and new in vitro transcriptases (reduced dsRNA production, vsw-3-RP, and T7 RNA polymerase mutants [55,56]) have emerged, signifying the maturation of mRNA vaccine production technologies.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that a mutant enzyme (T768) based on the T7 enzyme RNA polymerase capped efficiently and extensively reduced the amount of dsRNA, following HPLC purification [ 55 ]. The amount of dsRNA in mRNA transcribed by another in vitro transcriptase (VSW-3) encoded by a bacterial gene product from high salt is approximately less than 1/10 or even less than the dsRNA formed by transcription of the T7 enzyme [ 56 ]. In addition to improving mRNA purity, mutants of T7 transcriptase, such as a single mutation (S43Y), considerably improve transcription efficiency [ 57 ].…”
Section: Mrna Vaccine Optimizationmentioning
confidence: 99%
“…Accordingly, we concluded that the additional 6 novel enzymes identified in this study (Erwinia amylovora phage Era103, Pectobacterium phage DUPP II, Pectobacterium phage Jarilo, Delftia phage IME-DE1, Pseudomonas phage Henninger, Citrobacter phage CR8) are also likely to facilitate moderate-to-high mRNA production yields. While we cannot currently comment on the relative ability of these new polymerase to enhance product quality, previous work suggests they will generate variable levels of product-related impurities, such as dsRNA and truncated species (Lu et al, 2019;Wang et al, 2022;Xia et al, 2022;Zhu et al, 2013Zhu et al, , 2015. Indeed, this new library is particularly likely to exhibit differential bioproduction phenotypes, given that they were specifically selected based on sharing minimal amino acid sequence similarities.…”
Section: Cognate Promoter Prediction Is the Critical Limiting Factor ...mentioning
confidence: 98%
“…The available RNAP toolbox has recently been expanded by studies focussed on identifying and characterising individual enzymes with putative desirable bioproduction phenotypes. KP34 enhances 3' homogeneity of product molecules (Lu et al, 2019), VSW-3 reduces doubled stranded RNA (dsRNA) impurities (Xia et al, 2022), and Syn5 exhibits increased processivity (Zhu et al, 2013), as compared to that achieved with T7. While these hypothesis-driven approaches have successfully identified new biocatalysts with novel functionalities, only six characterized RNAPs are currently publicly available for mRNA manufacture (although we note that some additional unpublished enzymes may be utilised in industrial settings).…”
Section: Introductionmentioning
confidence: 99%